2021
DOI: 10.1002/jbm4.10503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Osteoporosis on Bone Morphometry and Material Properties of Individual Human Trabeculae in the Femoral Head

Abstract: Osteoporosis is the most common bone disease and is conventionally classified as a decrease of total bone mass. Current diagnosis of osteoporosis is based on clinical risk factors and dual energy X‐ray absorptiometry (DEXA) scans, but changes in bone quantity (bone mass) and quality (trabecular structure, material properties, and tissue composition) are not distinguished. Yet, osteoporosis is known to cause a deterioration of the trabecular network, which might be related to changes at the tissue scale—the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…In our survey, the mineral matrix ratio of femoral neck cortical bone decreased gradually from normal bone mass to severe osteoporosis. These suggest that the bone loss of femoral neck may be associated with the imbalance in the ratio between bone collagen and mineral, which may also affect bone strength in femoral neck [ 32 ]. Correlation analysis revealed that there is a significant relationship between the mineral matrix ratio and the L max of the femoral neck cortical bone, which further illustrated that the imbalance in the ratio between bone collagen and mineral lead to the changes of femoral neck macroscopic mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, the mineral matrix ratio of femoral neck cortical bone decreased gradually from normal bone mass to severe osteoporosis. These suggest that the bone loss of femoral neck may be associated with the imbalance in the ratio between bone collagen and mineral, which may also affect bone strength in femoral neck [ 32 ]. Correlation analysis revealed that there is a significant relationship between the mineral matrix ratio and the L max of the femoral neck cortical bone, which further illustrated that the imbalance in the ratio between bone collagen and mineral lead to the changes of femoral neck macroscopic mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Достатньо виражені та різноманітні біохімічні прояви інтоксикації алюмінієм [9,12]. Токсичність алюмінію багато в чому пов'язана з його антагонізмом щодо кальцію, магнію, фосфору, цинку та міді, а також зі здатністю утворювати сполуки з білками, накопичуватися в нирках [12], кістковій [7,10,14] і нервовій тканинах [6,11]. У травному тракті виявлено різні алюмінієві депо, на які суттєво впливають зміни рН у просвіті кишок, що забезпечує можливість його абсорбції, накопичення у тканинах або слизових оболонках і виведення з калом [9].…”
unclassified